PENERAPAN METODE PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATA PELAJARAN SISTEM PENGAPIAN SISWA KELAS XI SMK AL-MADANI KEPIL WONOSOBO TAHUN PELAJARAN 2016/2017 - Kukuh Tyas Widodo; Tarto Sentono (Universitas Sarjanawiyata Tamansiswa, 2017)
The objective of this study was to improve (1) learning activity and (2) learning achivement of ignition system by using problem based learning teaching method. The type of this study was an action research. Data collection method used ovservation and test. The research instrumens were leson plan, test, and observation guideline. Data analysis technique used a descriptive analysis and qualitative analyis to know the percentage of learning activity and learning achivement of ignition system. This study shows that (1) based on the result of observation in cycle I, the mean score of learning activity was 43.15% in low category in the interval antara 41% - 65%. The mean scoreof learning activity in cycle II was 71.37% in fair category in the interval antara 66% -74%. The mean score of learning activity in cycle III was 82.78% in high category in the interval antara 85% - 100%. (2) The use of problem based learning teaching method could improve learning achivement of ignition system. The improvement could be seen from the mean score of test of cycle I was 73.26 imprived in cycle II 80.39 and cycle III 88.77. The percentage of students who wete completed in learning in cycle I was 38.71% improved in cycle II becmae 87.10% and 96.8% in cycle III